Scalable synthesis of CuSn bimetallic catalyst for selective CO2 electroreduction to CO over a wide potential range. Issue 8 (6th January 2023) - Zhu, Zi-Chun; Ge, Jun-Yan; Qiao, Man; Yang, Xue-Li; Tang, Yu-Jia; Zhu, Dongdong; Chen, Ping
Abstract : A scalable, and cost-effective strategy was developed to prepare self-supported CuSn bimetallic catalyst, which can selectively reduce CO2 to CO at a wide potential range of 1100 mV. Abstract : A scalable, and cost-effective method was employed to prepare self-supported CuSn bimetallic catalyst on carbon paper. The obtained CuSn catalyst demonstrates high faradaic efficiency of CO around or above 90% at a broad potential range from −0.7 to −1.8 V vs. reversible hydrogen electrode, greatly surpassing Cu or Sn counterparts.